Fabrication and characterization of polyvinyl chloride/poly(styrene-co-maleic anhydride) intercalated functional nanobifiller-based composite paper. Issue 3 (2nd April 2016) - Khan, Dost Muhammad; Kausar, Ayesha; Salman, Syed M.
ABSTRACT: The resin infiltration technique was used for impregnation of graphene oxide (GO) and graphene oxide-functional carbon nanotube (GO-ox-CNT) with polyvinyl chloride (PVC) and poly(styrene- co -maleic anhydride) (PSMA) blend. Two series of buckypapers were prepared with GO and GO-ox-CNT content. The morphology of PVC/PSMA/GO composite paper was porous, while PVC/PSMA/GO-ox-CNT revealed exclusive morphology with GO islands and intercalated ox-CNT networks covered with PVC/PSMA. T max of PVC/PSMA/GO-ox-CNT 0.1 was 571°C, whereas PVC/PSMA/GO 0.1 had a lower value (559°C). T g of PVC/PSMA/GO-ox-CNT 0.1 was also higher (290°C). Cone calorimetric results showed a decrease in PHRR from 499 (blend) to 186 kW/m 2 with 0.3 g GO-ox-CNT.